2016
DOI: 10.22364/eeb.14.15
|View full text |Cite
|
Sign up to set email alerts
|

The diet composition of breeding Ospreys (Pandion haliaetus) in Latvia

Abstract: The diet composition of breeding Ospreys (Pandion haliaetus) was studied in several location in Latvia from 2009 to 2015 by determining food remains, intact or partly eaten fish in the nests, and photo and video materials from surveillance cameras that were set up at 14 nests. During the study period, information about 1501 Osprey prey specimens was collected from 119 nests and they were all fish. In total, 15 fish species were identified in Osprey diet, of which the most numerous was common carp (Cyprinus car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…swimming close to the bottom) such as tripodfish, groupers, flatheads, emperors, and seabreams. Kalvans and Bajinskis (2016) report that, in Latvia, ospreys essentially catch fish with a benthic lifestyle, such as carp (Cyprinus carpio, Carassius gibelio) and tench (Tinca tinca). They could be easily caught in fish ponds where the water is shallow.…”
Section: Taxonomic Diversity and Feeding Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…swimming close to the bottom) such as tripodfish, groupers, flatheads, emperors, and seabreams. Kalvans and Bajinskis (2016) report that, in Latvia, ospreys essentially catch fish with a benthic lifestyle, such as carp (Cyprinus carpio, Carassius gibelio) and tench (Tinca tinca). They could be easily caught in fish ponds where the water is shallow.…”
Section: Taxonomic Diversity and Feeding Behaviorsmentioning
confidence: 99%
“…1) found that mullet opercles and preopercles constitute almost 80% of the collected remains in Corsica (South-East France). Similarly, opercle bones are also among the dominant remains found in Finland, Latvia, and the Canarian Archipelago (Häkkinen, 1978;Siverio et al, 2011;Kalvans & Bajinskis, 2016). Prevost (1982: 87) indicates that opercles of even the smallest fish caught were removed in Senegal.…”
Section: Discarding Behaviorsmentioning
confidence: 99%